Peran Umkm Dalam Mendorong Pertumbuhan Ekonomi Bisnis Pada Kelurahan Betungan Kota Bengkulu) - Nadia Syaputri syaputri; Yuni Herlina; Mimpira Haryono (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in driving economic growth in Betungan Village, Bengkulu City. The study used a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation, then analyzed qualitatively and descriptively. The results indicate that MSMEs play a role in increasing community income, creating jobs, and driving local economic activity, despite still facing challenges in capital and marketing. It is concluded that MSMEs are the driving force of the local business economy in Betungan Village, Bengkulu City.